Creating instructional capacity a framework for creating academic press - Murphy, Joseph 1949- (Corwin, 2016)
"Technology and the age of information have forced educators to rethink how they can create a supportive culture and build academic press. School leaders who learn how to balance these ideas will build successful teams to meet today's standards"--Back cover.